2024
DOI: 10.1093/jisesa/ieae022
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with amitraz and thymol to manage Varroa destructor mites (Acari: Varroidae) in Apis mellifera honey bee colonies (Hymenoptera: Apidae)

Dan Aurell,
Clint Wall,
Selina Bruckner
et al.

Abstract: The parasitic mite Varroa destructor (Anderson and Trueman) is one of the greatest stressors of Apis mellifera (L.) honey bee colonies. When Varroa infestations reach damaging levels during fall, rapid control is necessary to minimize damage to colonies. We performed a field trial in the US Southeast to determine if a combination of registered treatments (Apivar, amitraz-based; and Apiguard, thymol-based) could provide rapid and effective control of Varroa. We compared colonies that received this combination t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Another pesticide-based Varroa control method was investigated by Aurell and colleagues ( 2024 ), who found that combining amitraz-based treatments with thymol-based treatments was particularly effective for Varroa control in the Southeastern United States. These findings may allow beekeepers to decrease the selection pressure on Varroa that has led to resistance ( Rinkevich 2020 ), although the resulting drop in bee population after combined treatments calls for further study.…”
Section: Potential Stress Mitigation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pesticide-based Varroa control method was investigated by Aurell and colleagues ( 2024 ), who found that combining amitraz-based treatments with thymol-based treatments was particularly effective for Varroa control in the Southeastern United States. These findings may allow beekeepers to decrease the selection pressure on Varroa that has led to resistance ( Rinkevich 2020 ), although the resulting drop in bee population after combined treatments calls for further study.…”
Section: Potential Stress Mitigation Methodsmentioning
confidence: 99%
“…However, we have made relatively less progress in discerning how nonchemical disease, pest, and pathogen control techniques can effectively be used or paired with chemical control techniques to form sustainable best management practices that will be embraced by beekeepers. This work has begun for Varroa ( Berry et al 2023 , Aurell et al 2024 , Plamondon et al 2024 ), but continues to be needed for other pests and diseases such as EFB ( Grant et al 2021 ), American foulbrood ( Zabrodski et al 2022 ), chalkbrood ( Aronstein and Murray 2010 ), small hive beetles ( Mustafa et al 2014 ), Vairimorpha (formerly Nosema ) spp. ( Goblirsch 2018 ), viruses ( Beaurepaire et al 2020 ), and emerging parasites of concern such as Lotmaria passim ( Gomez-Moracho et al 2020 ) and Tropilaelaps spp.…”
Section: Conclusion and Future Research Needsmentioning
confidence: 99%